2022
DOI: 10.11591/ijece.v12i3.pp2839-2846
|View full text |Cite
|
Sign up to set email alerts
|

Simulation for predictive maintenance using weighted training algorithms in machine learning

Abstract: <span>In the production, the efficient employment of machines is realized as a source of industry competition and strategic planning. In the manufacturing industries, data silos are harvested, which is needful to be monitored and deployed as an operational tool, which will associate with a right decision-making for minimizing maintenance cost. However, it is complex to prioritize and decide between several results. This article utilizes a synthetic data from a factory, mines the data to filter for an ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Artificial intelligence offers tools that are completely decoupled from the structure of the system, not requiring prior modeling of the latter and allowing real-time monitoring of its evolution, and its tools use several algorithms, among others, those applied for maintenance [22].…”
Section: Ai Algorithms Applied To Maintenancementioning
confidence: 99%
“…Artificial intelligence offers tools that are completely decoupled from the structure of the system, not requiring prior modeling of the latter and allowing real-time monitoring of its evolution, and its tools use several algorithms, among others, those applied for maintenance [22].…”
Section: Ai Algorithms Applied To Maintenancementioning
confidence: 99%
“…Based on the evidence from Figure 1, MTBF (Main Time Between Failure) is the most popular KPI in the field of asset valuation due to its easy accessibility and understanding (Jittawiriyanukoon and Srisarkun, 2022). In addition, asset performance monitoring is of great use in predicting any potential asset behavior, problems and losses (Márquez et al ., 2019), followed by asset reliability, availability and efficiency with the same objective (Liu et al ., 2022; Ruschel et al ., 2020; Yu et al ., 2019).…”
Section: State Of the Artmentioning
confidence: 99%
“…Ghosh et al [17] used dataset Wisconsin breast cancer database (WBCD) to introduced a novel approach by using severial algorithm like LR, DT, RF, SVM and KNN and used Least Absolute Shrinkage and Selection Operator (LASSO) as feature selction and result show RF was best accurate by 99.41%; Jittawiriyanukoon and Srisarkun [18]. They used location data, machines, statistics, and downtime from a data-mining plant using artificial intelligence and machine learning to develop a decision support strategy; scheduling a maintenance plan by using open source software for replacing the shortcut of maintenance planning and scheduling; on data mining, 3 promising training algorithms are used for insightful data as a result precision numbers have been obtained; Alalwan et al [19] two data mining algorithms were used a self-organizing map and a RF for diabetes diagnosis; the results have shown that they can provide services in the health care sector to make effective decisions; Saranya and Pravin [20] in this work, they comprehensively study the different strategies used to predict diseases by applying several mining algorithms to improve prediction to reduce hospital admissions and reduce patient costs.…”
Section: Introductionmentioning
confidence: 99%